2012
DOI: 10.1177/014556131209100418
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization of Blom-Singer Indwelling Voice Prostheses in Laryngectomized Patients: A Perspective from India

Abstract: We analyzed a series of adults with an implanted voice prosthesis that had malfunctioned and required removal as a result of the attachment and growth of microorganisms. Our goal was to determine the characteristics of these colonizing microbes. We swabbed the esophageal side of each prosthesis to obtain microbial flora for analysis with standard culture media. In all, we studied 22 prostheses in 18 patients (3 patients had received multiple prostheses). We found mixed contamination (both yeast and bacteria) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The most prominent bacteria found in our specimens were P. aeruginosa, K. pneumoniae and S. aureus, all three facultative anaerobes and part of the normal oral or skin flora. In accordance with our results, it has been reported previously that these bacteria are part of the microbial plaque on VPs, [6, 14, 15, 17, 21] including normal oral or periodontopathogenic flora, such as P. aeruginosa [19]. It has been hypothesized that the interaction with bacterial strains, such as S. aureus enhances the initial steps of plaque formation and ultimate device failure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most prominent bacteria found in our specimens were P. aeruginosa, K. pneumoniae and S. aureus, all three facultative anaerobes and part of the normal oral or skin flora. In accordance with our results, it has been reported previously that these bacteria are part of the microbial plaque on VPs, [6, 14, 15, 17, 21] including normal oral or periodontopathogenic flora, such as P. aeruginosa [19]. It has been hypothesized that the interaction with bacterial strains, such as S. aureus enhances the initial steps of plaque formation and ultimate device failure.…”
Section: Discussionsupporting
confidence: 92%
“…Reported bacterial contaminants receive far less attention, and those reported mostly include commensal oral microflora, predominantly S. aureus , Pseudomonas sp ., Enterobacter sp ., Klebsiella sp ., R. dentocariosa , and Proteus sp . [4, 5, 1317, 20, 21]. However, a potential adhesive interaction between those and the colonizing Candida species, especially S. aureus, has been proposed [14, 16].…”
Section: Introductionmentioning
confidence: 99%
“…This, together with its action against C. albicans biofilms presented here, highlights the potential for 2-DG to be used an anti-biofilm therapeutic. It may be particularly useful for medical devices such as voice prostheses which are situated in CO 2 -rich environments in the body and are often colonised by a mixture of bacterial and fungal species 77787980 . It’s important to note however that 2-DG was unable to eradicate C. albicans biofilm growth completely.…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal and fungicidal activity against the main pathogens responsible for the fouling of the implant including C. albicans may also be mediated through lactoferrin and anti-Candida immunoglobulin A antibodies in milk [15]. Consumption of dairy products in form of yoghurt and buttermilk includes the normal diet in India and Sayed et al [16] have now shown a fairly long average prosthesis lifetime (201 days) in a series of removed voice prostheses in Indian population as a probable effect of this dietary element. Basically fermented milk products provide an easily accessible, simple supplement to a daily diet that could work as a preventive measure for frequent replacements of the voice prostheses in a way the Indian clinical experience suggests.…”
Section: Biofilm In Voice Prostheses and Tracheal Tubesmentioning
confidence: 99%